Herbigation through drip irrigation systems in citrus orchards in Spain - Gómez-De-Barreda, Diego; Del-Busto, Angelina; Cebolla, Vicent; Ferrer-Talón, Pedro J. (2017)
First herbigation trials in citrus were made with EPTC, in flood irrigation, in the early seventies. The low persistence of EPTC in soil, made the technique too expensive and it was almost abandoned. Afterwards, trifluralin was applied in the water with better success. The interest in herbigation in Spain is the result of the success of drip irrigation in the eighties. Data from several orchards where drip irrigation is performed, derived from a survey of grovers shown in this paper. Only ten percent of surveyed citrus farmers use drip herbigation. Bromacil, diuron, oxyfluorfen, norflurazon, simazine, terbuthylazine, and terbacil are the major herbicides applied in this technique. Different reasons are shown for the decision not to use herbigation. Weed control in the orchard, in addition to injection through the irrigation lines, needs complementary treatments in the non wetted area. One of the most serious drawbacks found is poor drip discharge uniformity in many orchards. Because herbicide degradation is faster in the bulb zone, the injection is usually applied more than three times a year.